Cerium modified minerals for eco-friendly anticorrosive paints - Roselli, Sol Natacha (2013)
This paper deals with the replacement of zinc phosphate by a natural zeolite, modified with Ce(III) ions. The inhibitive properties of rare earth metals are very well known and the zeolite would act as a “carrier” for these ions. Alkyd paints were formulated replacing totally and partially zinc phosphate by the Ce-exchanged zeolite. Paints anticorrosive performance was evaluated by electrochemical impedance (EIS) and electrochemical noise measurements (ENM). Results showed that zinc phosphate could be partially replaced by the modified zeolite maintaining acceptable anticorrosive properties.